KAJIAN STRUKTUR PENGAMAN PANTAI SIGANDU, BATANG - Sidiq Leonanda Widhianto; Dicki Kharisma; Suharyanto Suharyanto; Siti Hardiyati (Departemen Teknik Sipil, Fakultas Teknik Universitas Diponegoro, 2014)
Generally, the problems that occur in Sigandu Beach - Batang is abrasion, resulting in damage to the beach. This has an impact on the coastal areas along the coast of Sigandu, among others land that has been covered with sea water exceeds 2 m within 5 months, trees and houses around the beach collapsed due to erosion beach by sea water. The information and supporting data are collected from several literatures, interview, laboratory research, and a collection of documents from several institutions, including the Department of Marine and Fishery of Batang, BPDP and BPPT of Yogyakarta in 2013, BMKG Climatology Station in Semarang, Soil Mechanics Laboratory of Diponegoro University and several other institutions. The dominant wind direction effect used in the calculations come from the Northwest and North. Wave height representative used a H33% at 2,94 m and a representative period T33% 8,82 seconds. Sea level caused of tide by the calculation of admiralty generating value HWL =+0.49 m; MSL = ± 0.00 m; LWL = -0.49 m. The tide of Sigandu Beach included in mixed tide prevailing semidiurnal. In the calculation, the wave breaking occurs at a depth of 4.22 m at a distance of ± 787.09 meters from the shoreline. Based on studies of the selection safety structure from some aspects of the Sigandu Beach, the elected lower threshold breakwater structure (Pegar) Geotube. Because a bad soil conditions in Sigandu Beach, then there needs to be retaining structures on Geotube is by giving it a pile of bamboo and bamboo mattresses that had been assembled under the structure of Geotube. Geotube structure is composed of Giant Sand Bag with dimension length 20 m, width 2 m and 1,5 m high with a weight of 6 tons/m' and Sand Bag with dimension length 2,2 m, width 1,4 m, and height 0,4 m with a weight of 1,12 tons/m'. To be expected to form the salient, the structure compiled in series with spacing distance of 10 m with a 100 m length of the building and placed 75 m from the shoreline.